2022
DOI: 10.1093/polsoc/puab009
|View full text |Cite
|
Sign up to set email alerts
|

Re-thinking the coronavirus pandemic as a policy punctuation: COVID-19 as a path-clearing policy accelerator

Abstract: This article joins with others in this special issue to examine the evolution of our understanding of how the coronavirus disease (COVID)-19 pandemic impacted policy ideas and routines across a wide variety of sectors of government activity. Did policy ideas and routines transform as a result of the pandemic or were they merely a continuation of the status quo ante? If they did transform, are the transformations temporary in nature or likely to lead to significant, deep and permanent reform to existing policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 75 publications
1
56
0
2
Order By: Relevance
“…Menschner and Maul [ 76 ] highlighted how implementing trauma-informed approaches in healthcare systems “require a paradigm shift”(p. 10). The punctuated equilibrium of COVID-19 presents an opportunity for policy change at HEIs, for which research is needed to inform [ 77 ]. Thus, this serves as a call to action in higher education; a call to resist blissful ignorance and challenge history by naming trauma for what it is and addressing it, so that students can reach their full learning potential.…”
Section: Discussionmentioning
confidence: 99%
“…Menschner and Maul [ 76 ] highlighted how implementing trauma-informed approaches in healthcare systems “require a paradigm shift”(p. 10). The punctuated equilibrium of COVID-19 presents an opportunity for policy change at HEIs, for which research is needed to inform [ 77 ]. Thus, this serves as a call to action in higher education; a call to resist blissful ignorance and challenge history by naming trauma for what it is and addressing it, so that students can reach their full learning potential.…”
Section: Discussionmentioning
confidence: 99%
“…Although the COVID-19 crisis has caused extensive and in-depth impacts in different policy areas of countries around the world, it is not yet a paradigm shift in the traditional sense of a critical juncture [ 38 ]. Technology-driven governance reflects the basic orientation of adaptive transformation of social governance [ 39 ].…”
Section: Research Methods and Analytical Frameworkmentioning
confidence: 99%
“…Path creation-related concept is centred on the premise that policy entrepreneurs shape paths, rather than exogenous shocks, by initiating processes that actively shape emerging social practices (cf. Hogan et al, 2022). In our context, new 'potential' paths are not simply emerging as a result of shocks associated with COVID-19, but rather as a result of strategic agencies creatively modifying policy content based on embedded cultural values, previous practices, and policy learning (cf.…”
Section: Theorising Policy Responsesmentioning
confidence: 99%
“…A review of various literature Karnøe, 2001, 2005;Garud et al, 2010) has shown that the path creation process is characterised by a deviation of the policy from the established path and principle, while discontinuing the previous one. Recently, Hogan et al (2022) defined it as 'novel or innovative actions creating new paths' (p. 43). The path creation process is characterised by an extensive modification and even a replacement of the main ideas and features of policy with a new one in a very short period of time, as opposed to displacement, path-breaking, and path-switching, which requires a slow-moving, long-term process.…”
Section: Theorising Policy Responsesmentioning
confidence: 99%
See 1 more Smart Citation